(Re)thinking Body-Technology Relations with Michel Serres - Ian Tucker (Media Theory)
This paper highlights several key principles of the work of Michel Serres and considers them in relation to life in contemporary socio-technical worlds, e.g. notions of relationality, noise, bodies, sense and data. A journey with Serres involves seeking novelty in spaces ‘outside’ of existing knowledge producing practices. This paper highlights how, for Serres, mediation as noise does not operate via a singular universal interface, but is multiple and processual – in essence, everything is mediation. Using contemporary examples of new technologies (e.g. AI and play writing; AI and emotion) the paper considers the value of a Serrian mode of thought for understanding emerging relations between bodies and technologies. It concludes with acknowledging the growing political focus on Serres’ later work, in which he became increasingly concerned to (re)define the contract between humanity and the world. His notion of appropriation through pollution encompasses notions of information and data as forms of algorithmic appropriation, as much if not more, than physical pollution.